Relief of persistent atypical atrial flutter: experience with the use of niferidil - E. A. Zakharyan; D. V. Shatov; A. O. Povoroznyj; T. B. Bujar (Рациональная фармакотерапия в кардиологии)
An increase in life expectancy contributes to a steady growth  of diseases of the cardiovascular system. In recent years, there has been a stable increase in the prevalence  of rhythm  disturbances  in the population.  Fibrillation and atrial flutter are among  the most common  causes  of a decrease  in the quality of life and an increase in mortality. However, the effectiveness  of various methods of treatment is not absolute,  and therefore the development and introduction  of new antiarrhythmic drugs  is particularly  relevant. Thus,  the use of a class III antiarrhythmic drug  (niferidil) is of unconditional interest, and literature data describing the effectiveness  of its use for the relief of atypical atrial flutter are extremely few. The article presents a case of successful  relief of a persistent form of atypical atrial flutter in a 79-year-old patient using three consecutive intravenous injections of niferidil at a dose of 10 mcg/kg with a 15-minute interval in 19 hours after the start of therapy. The presented clinical case confirms the effectiveness of drug cardioversion with the use of niferidil and makes it possible to consider it as an alternative to electrical cardioversion  in patients with atypical atrial flutter.